Systematic review of the effectiveness of training programs in writing for scholarly publication, journal editing, and manuscript peer review (protocol) - Galipeau, James; Moher, David; Skidmore, Becky; Campbell, Craig; Hendry, Paul; Cameron, D W; Hébert, Paul C; Palepu, Anita (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background An estimated $100 billion is lost to ‘waste’ in biomedical research globally, annually, much of which comes from the poor quality of published research. One area of waste involves bias in reporting research, which compromises the usability of published reports. In response, there has been an upsurge in interest and research in the scientific process of writing, editing, peer reviewing, and publishing (that is, journalology) of biomedical research. One reason for bias in reporting and the problem of unusable reports could be due to authors lacking knowledge or engaging in questionable practices while designing, conducting, or reporting their research. Another might be that the peer review process for journal publication has serious flaws, including possibly being ineffective, and having poorly trained and poorly motivated reviewers. Similarly, many journal editors have limited knowledge related to publication ethics. This can ultimately have a negative impact on the healthcare system. There have been repeated calls for better, more numerous training opportunities in writing for publication, peer review, and publishing. However, little research has taken stock of journalology training opportunities or evaluations of their effectiveness. Methods We will conduct a systematic review to synthesize studies that evaluate the effectiveness of training programs in journalology. A comprehensive three-phase search approach will be employed to identify evaluations of training opportunities, involving: 1) forward-searching using the Scopus citation database, 2) a search of the MEDLINE In-Process and Non-Indexed Citations, MEDLINE, Embase, ERIC, and PsycINFO databases, as well as the databases of the Cochrane Library, and 3) a grey literature search. Discussion This project aims to provide evidence to help guide the journalological training of authors, peer reviewers, and editors. While there is ample evidence that many members of these groups are not getting the necessary training needed to excel at their respective journalology-related tasks, little is known about the characteristics of existing training opportunities, including their effectiveness. The proposed systematic review will provide evidence regarding the effectiveness of training, therefore giving potential trainees, course designers, and decision-makers evidence to help inform their choices and policies regarding the merits of specific training opportunities or types of training.